Transport Phenomena in Multiphase Systems (Advanced Structured Materials,, 2018)
This book presents a collection of recent contributions in the field of transport phenomena in multiphase systems, namely, heat and mass transfer. It discusses various topics related to the transport phenomenon in engineering (including state-of-the-art, theory and applications) and introduces some of the most important theoretical advances, computational developments and technological applications in multiphase systems domain, providing a self-contained key reference that is appealing to scientists, researchers and engineers alike. At the same time, these topics are relevant to a variety of scientific and engineering disciplines, such as chemical, civil, agricultural, and mechanical engineering. .